Sophie's choice [compact disc, unabridged] - Styron, William, 1925-2006 (BBC Audiobooks America, 2003)
Three stories are told: that of a young Southerner, Stingo, who wants to become a writer; of a turbulent love-hate affair between Nathan Landau, a brilliant Jew, and a beautiful Polish woman, Sophie Zawistowski; and of an awful wound in that woman's past--one that propels both Sophie and Nathan toward destruction.